2009
DOI: 10.1097/prs.0b013e31819f2928
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Irradiated Head and Neck Tissues by Autologous Fat Transplantation

Abstract: Fat tissues can be successfully transplanted into irradiated areas, inducing both aesthetic and functional improvement. The cellular and/or tissular mechanisms underlying these changes need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(106 citation statements)
references
References 28 publications
2
93
1
10
Order By: Relevance
“…Auch die histomorphologischen Kennzeichen von bestrahlten Hautarealen, wie Fibrose und reduzierte Mikrovaskularisation, scheinen Fettinjektionen günstig zu beeinflussen [32]. In den bisherigen klinischen Studien zur Injektion von Fett bzw.…”
Section: Rolle Adipogener Stammzellenunclassified
“…Auch die histomorphologischen Kennzeichen von bestrahlten Hautarealen, wie Fibrose und reduzierte Mikrovaskularisation, scheinen Fettinjektionen günstig zu beeinflussen [32]. In den bisherigen klinischen Studien zur Injektion von Fett bzw.…”
Section: Rolle Adipogener Stammzellenunclassified
“…Despite of fat being biocompatible, non-immunogenic and a natural filler, concerns on its oncological safety persist in breast cancer patients undergoing mastectomy and reconstruction (3)(4)(5)(6). In vitro studies have shown the lipoaspirate to be a bioactive substance whose adiposederived stem cells (ADSCs) are capable of cell stimulation and tissue regeneration by the secretion of numerous factors (7)(8)(9) that also promote cancer growth, angiogenesis and alter the antitumor immune response (10) when in close vicinity to breast cancer cells. Thus experimental studies demonstrated a potential risk of lipofilling to cause cancer recurrence as ADSCs may stimulate quiescent cancer cells still resident after surgery (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…La tolérance du lapin aux manipulations d'anesthésie et d'irradiation répétitives a été optimale. D'autres études ont été réalisées sur des fémurs de rats [5] ou des beagles. Le lapin semble être un compromis intéressant entre la fiabilité de l'étude, le coût et la simplicité des manipulations.…”
Section: Discussionunclassified
“…Certains éléments de sa pathogénie restent toujours inconnus. De nombreuses études ont été menées pour évaluer les effets de la radiothérapie sur le tissu osseux, mais la plupart d'entre elles concernaient des fémurs de lapins ou de rats [4,5]. Une étude canadienne a mis au point un modèle d'irradiation du complexe orbito-zygomatique chez le lapin immature (7 semaines) [6] ; dans ce modèle, deux doses ont été délivrées, 25 et 35 Gy.…”
unclassified